THE PRELIMINARY STUDIES OF ENVIRONMENTAL ETHICS IN JUNIOR AND SENIOR HIGH SCHOOL STUDENTS THROUGH ENVIRONMENTALLY SOUND LEARNING - Mohamad Khoirul Anam; Sudarti Sudarti (ScienceEdu: Jurnal Pendidikan IPA, 2020)
Learning is an activity that has important potential to instill scientific attitudes and positive attitudes in students. Learning activities in schools can provide insight for students in several fields, one of which is the environment. As is known, environmental problems are problems that are always found and tend to accompany human behavior and activities. The problem of cleanliness, order, and rubbish is a complicated thing that is entrenched in the current era supported by the increasingly high consumption of human consumption. For this reason, ethics-based learning needs to be applied in teaching and learning activities in the classroom. In the initial study of this study using the observation method with a questionnaire aimed to get students' responses related to environmental ethics.